Comparison of breast‐conserving surgery without radiotherapy and mastectomy in the treatment of elderly patients with early breast cancer: A PSM and SEER database study - Baiyang Fu; Xi Chen; Wenlong Liang; Yao Wang; Yuan Yao; Jianguo Zhang (Cancer Medicine, 2023)
Abstract Background At present, there is no research on which surgical method can lead to a better prognosis in elderly patients with early breast cancer. The purpose of this study was to establish a nomogram to predict the survival outcome of elderly patients with early breast cancer and to compare the prognosis of the breast‐conserving surgery (BCS) group who did not receive postoperative radiotherapy and the mastectomy group through risk stratification. Methods This study included patients with early breast cancer aged ≥70 years from the Surveillance, Epidemiology, and End Results database (n = 20,520). The group was randomly divided into a development cohort (n = 14,363) and a validation cohort (n = 6157) according to a ratio of 7:3. Risk factors affecting overall survival (OS) and breast‐cancer‐specific survival (BCSS) were analyzed using univariate and multivariate Cox regression. Present results were obtained by constructing nomograms and risk stratifications. Nomograms were evaluated by the concordance index and calibration curve. Kaplan–Meier curves were established based on BCSS and analyzed using the log‐rank test. Results Multivariate Cox regression results showed that age, race, pathological grade, T and N stages, and progesterone receptor (PR) status were independent risk factors for OS and BCSS in the BCS group and mastectomy group. Subsequently, they were incorporated into nomograms to predict 3‐ and 5‐year OS and BCSS in patients after BCS and mastectomy. The concordance index was between 0.704 and 0.832, and the nomograms also showed good calibration. The results of risk stratification showed that there was no survival difference between the BCS group and the mastectomy group in the low‐risk and high‐risk groups. In the middle‐risk group, BCS improved the BCSS of patients to a certain extent. Conclusion This study constructed a well‐performing nomogram and risk stratification model to assess the survival benefit of BCS without postoperative radiotherapy in elderly patients with early breast cancer. The results of the study can help clinicians analyze the prognosis of patients and the benefits of surgical methods individually.